2012
DOI: 10.1063/1.3677267
|View full text |Cite
|
Sign up to set email alerts
|

Bremsstrahlung of fast electrons in long air gaps

Abstract: The results of an experiment on discharges in long atmospheric pressure air gaps at a pulsed voltage of amplitude up to 800 kV and risetime 150–200 ns have been analyzed. In the experiment, a radiation pulse of photon energy >5 keV and duration 10–20 ns was observed. In analyzing the experimental data it was supposed that a streamer is a plasma protrusion whose surface is equipotential to the cathode surface. It has been shown that the x-ray pulse results from the switch of electrons into the mode of "r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Currently the studies of formation and propagation of streamer at breakdown of elevated pressure gases are conducted actively [17][18][19][20][21][22][23][24][25]. The streamer propagation velocity was shown to increase with applied voltage [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently the studies of formation and propagation of streamer at breakdown of elevated pressure gases are conducted actively [17][18][19][20][21][22][23][24][25]. The streamer propagation velocity was shown to increase with applied voltage [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…In [23] streamer discharge operated at applying two consecutive positive highvoltage pulses to a point-plane gas-filled gap was investigated. The appearance of runaway electrons during streamer propagation was discussed in [24,25]. At REP DD formation, the overlap of many electrons avalanches occurs and an ionization wave with transverse dimensions of the order of a centimeter forms [3,5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] An x-ray flash occurred within about 280 ns from the beginning of the voltage pulse; the flash duration was a few nanoseconds. Its occurrence was associated with the evolution of both cathode-initiated and anode-initiated streamers.…”
mentioning
confidence: 99%
“…The streamer length was measured by the discharge cutoff method, 43 and at the instant that an x-ray flash occurred the characteristic dimensions of the anode-directed streamers were: radius r s no more than 0.5 mm and length L s $ 1.5-2.5 cm. A numerical simulation [40][41][42] has shown that with these streamer dimensions an electron with energy of several electron-volts injected in a gap from the streamer surface can switch in the continuous acceleration mode. For this 043105-2…”
mentioning
confidence: 99%
See 1 more Smart Citation